APPLICATION OF EEG FEEDBACK FOR THE CORRECTION OF PSYCHOEMOTIONAL STATE OF CHILDREN - Ye. V. Eismont; T. A. Aliyeva; N. V. Lutsyuk; V. B. Pavlenko (Бюллетень сибирской медицины)
Evaluated the efficacy of neurofeedbacktherapy to normalize the psychoemotional state of children. Trained parameters of EEG were the amplitude of alpha-rhythm, the ratio of amplitudes of alphaand theta-rhythms, sensorimotor and theta-rhythms. In the experimental group showed an increase in the trained parameters of the electroencephalogram, reduced anxiety, “feelings of inferiority” and improvement of voluntary attention. The results indicate the feasibility of neurofeedbacktherapy to optimize the psychoemotional state of children.